Synthesis, antimicrobial activity and molecular docking of novel benzimidazole conjugated 1,2,3-triazole analogues - Mallikanti, Veerabhadraiah; Thumma, Vishnu; Matta, Raghavender; Valluru, Krishna Reddy; Konidena, Lakshmi Narayana Sharma; Boddu, Lakshmi Satya; Pochampally, Jalapathi (Chemical Data Collections, 2023)
A library of novel benzimidazole based 1,2,3-triazoles were synthesized by a series of reactions containing Suzuki coupling, cyclization and microwave assisted copper catalyzed click chemistry. All compounds 9(a-l) were screened for their antimicrobial activity against two gram positive Staphylococcus aureus and Bacillus subtilis and two gram negative Escherichia coli and Pseudomonas aeruginosa bacteria, and two fungal strains of Candida albicans and Aspergillus niger. Compounds 9b (2-methylbenzyl), 9e (2-trifluromethylbenzyl) and 9l (4-trifluormethylphenyl) have indicated notable antibacterial activity against E. coli compared to standard reference Ampicillin. Compounds 9i (3-fluorobenzyl) and 9k (3-cyanobenzyl) showed top activity against P. aeruginosa, S. aureus and B. subtilis with reference to Ampicillin. Compounds 9i (3-fluorobenzyl), 9j (4-fluorobenzyl) and 9k (3-cyanobenzyl) established potent activity against both the fungal strains compared to standard drug Griseofulvin. Molecular docking studies were performed against glucosamine-6-phospate synthase of E. coli and secreted aspartic proteinase of C. albicans to understand the binding affinity and interactions of compound against target receptors. [Display omitted]